Public Interest in the Context of State Regulation: Analysis and Development of the Concept - Korsakaitė, Diana (Ekonomika, 2006)
Modern state has a distinction of possessing an amplified regulatory system - in practice it is difficult to name at least one industry or economic activity left without regulatory oversee. A close look at regulatory activities, especially regulatory activities in infrastructure industries, would suggest that a difference between public interest and economics has faded out (Kessides, Willing, 1995; Longley, 2003); other papers argue that often a regulatory institution is left to decide on its own what exactly “public interest”, which is supposed to be defended by this institution, means (e.g., Condon, 2003). From the empirical view, in these cases the public interest’s interpretation, which goes as a basis for regulatory decisions, might not coincide with the public interest per se; and even more, without a clear formulation and treatment of public interest, it might be misused at the stage of development as well as at the stage of implementing the regulatory policy. From the theoretical view, a distinct concept of public interest is relevant with regard to the fact that a major part of regulatory theories use the notion of public interest to justify the regulation as such, however, those theories do not analyze the public interest leaving it to be done by political science. The aim of this research was, with regard to achievements published in the theoretical literature, to provide a revised concept of public interest, which (the concept) would be correct in the view of political science and would be operational in the view of management for the purposes to employ it in the regulated industry. The research has justified the importance of a correct concept of public interest in the context of state regulation, analyzes the notion of public interest with regard to the four main historically developed approaches, analyzes the modern notion of public interest, and a revised concept of public interest is developed here; finally, the relevance of the revised concept of public interest to be used in a regulated industry is evaluated in the view of management. The first chapter analyzes the conception of the state regulation - a number of definitions of regulation are provided and three meanings of “regulation” are distinguished (a set of norms and specific prescriptions; state intervention of all kinds or the deliberate influence by the state; all the forms of social control disrespectfully of who implements it). The chapter also deals with regulatory theories - a dualistic-approach taxonomy is developed and two theories of regulation (those of public interest and reformulated public interest) are analyzed in detail. The analysis provided in this chapter enabled to conclude that regulatory theories, justifying regulation as a purpose of implementation of public interest, are the full·fledged stream of theoretical regulatory thought. Despite the fact that recently this stream acquires less attention by theoreticians, governments, planning and implementing the regulation of the economy and its reforms, more often than ever use the approach of regulation for the public interest sake and the out-flowing argumentation. Therefore, analysis of public interest remains an important component of the theoretical backgrounding of regulation. The second chapter provides the genesis and critics of the notion of public interest with regard to the four main historically developed approaches. The historical analysis of public interest has shown that none of the four approaches has provided a public interest concept that would be clear, universal and ready for effective usage within regulatory systems. The Public Contract approach clarified the discrepancy of public interest and private interest, emphasized the supremacy of the public interest over all the other interests, which (the supremacy) is achieved either by consensus or under compulsion; the approach did not elaborated on what exactly the public interest is. The Doctrine of Utilitarianism determined, how to measure the public interest, and endowed the mandate to implement public interest to administration, but this doctrine did not highlighted any possibility to eliminate the conflict between the public and the private interests. In the Laissez-Fair Doctrine, the public interest was an approach as the laissez-fair itself, i.e. the spontaneous satisfaction of interests of all the participants of the process. The forth approach to the public interest - as a goal of a higher level together with safeguarding the particular elements of society - was supposed to bring the benefit for all; however, this theoretical interpretation was convenient to widen the borders of state’s intervention and to develop a nannystate. After the outcomes, their scale and directions were fully realized; a theoretical stream, completely denying the public interest as such, emerged. The critics of the traditional notion of public interest was structured into four main arguments: the (i) notion is indefinite, therefore it leaves space for conflicts; (ii) the indefiniteness of the notion necessitated a wider usage of the notion aiming to cover narrowed objectives, i.e. public interest became an outcome of activities instead of being a reason for it; (iii) the broad-brush nature of public interest stipulated oppression over individua1s and minorities, executed by collective organizations, (iv) the broad-brush nature also menaced individuality, variety, personal freedom and self-expression. The third chapter elaborates on the modem understanding of public interest, mainly with regard to the reborn liberal interpretation. The revised concept of public interest is formulated as follows: public interest is an overall, nonnative, conservative and equally to all applicable instrument, in the form of abstract norms providing better conditions to everyone for securing their own interests while utilizing their knowledge and their abilities in possession. This revised concept resolves the critical aspects applied to the traditional notion, and the elaboration is provided. Finally, the evaluation of the relevance of the revised concept for its use in a regulated industry is made, and the finding is that the revised concept of public interest is operational in the context of state regulation and is correct in the view of political science.